Paliperidone Palmitate in an Adult with Asperger‘s Syndrome - Antunes-Duarte, Tiago (2020)
Asperger’s syndrome is a disorder characterized by impaired social interaction and a pattern of stereotyped behaviors. These include repetitive behaviors, irritability, aggressiveness, hyperactivity and inattention. The treatment of behavioral symptoms is a challenge, with few studies on the effectiveness of different therapeutic approaches. This article is the first description of the successful use of monthly paliperidone palmitate in the treatment of behavioral symptoms in an adult with Asperger’s syndrome.